Adhesion characteristics of graphene oxide modified asphalt unveiled by surface free energy and AFM-scanned micro-morphology. (30th May 2020) - Zhu, Juncai; Zhang, Kun; Liu, Kefei; Shi, Xianming
Graphical abstract: Highlights: GO can significantly increase the surface free energy of asphalt and weaken the effect of aging on the SFE of asphalt. GO can improve the asphalt-aggregate adhesion and the moisture resistance of asphalt mixture. GO can improve the nano roughness of asphalt surface. SBS + GO modified asphalt can meet the basic requirements of high-viscosity asphalt for OGFC. Abstract: Graphene oxide (GO) is a promising nano-material to modify asphalt used in pavement. This work aimed to evaluate the feasibility of GO modified asphalt for the preparation of a high-viscosity asphalt used in open-graded friction course (OGFC). The adhesion characteristics and micro-morphology of the GO modified asphalt were evaluated using the sessile drop method and atomic force microscope (AFM). The addition of no more than 0.2 wt% GO notably increased the surface free energy of an asphalt and its dispersive and polar components and weakened the aging effects on the surface free energy of the asphalt. GO increased the adhesion work between asphalt and aggregate, with minimal influence on the spalling work. Thus, it remarkably enhances the asphalt-aggregate adhesion to improve moisture resistance of asphalt mixture. Limestone and granite aggregates exhibited the highest and lowest asphalt-aggregate adhesion, respectively, and basalt aggregate lied in between. The AFM observations revealed that GO can change the microstructure of asphalt and enhance the asphalt-aggregate adhesion. The adhesion and moisture resistance of styrene–butadienestyrene copolymer (SBS) + GO modified asphalt reached the requirements of high-viscosity asphalt and can be used in OGFC pavement, whereas the GO modified 70# asphalt requires further modification.